Cardiac rehabilitation in German speaking countries of europe: evidence-based guidelines from Germany, Austria and Switzerland LLKardReha-DACH, Part 2 - Schwaab, Bernhard; Bjarnason-Wehrens, Birna; Meng, Karin; Albus, Christian; Salzwedel, Annett; Schmid, Jean-Paul; Benzer, Werner; Metz, Matthes; Jensen, Katrin; Rauch, Bernhard; Bönner, Gerd; Brzoska, Patrick; et al. (Journal of Clinical Medicine, 2021)
Background: Scientific guidelines have been developed to update and harmonize exercise based cardiac rehabilitation (ebCR) in German speaking countries. Key recommendations for ebCR indications have recently been published in part 1 of this journal. The present part 2 updates the evidence with respect to contents and delivery of ebCR in clinical practice, focusing on exercise training (ET), psychological interventions (PI), patient education (PE). In addition, special patients’ groups and new developments, such as telemedical (Tele) or home-based ebCR, are discussed as well. Methods: Generation of evidence and search of literature have been described in part 1. Results: Well documented evidence confirms the prognostic significance of ET in patients with coronary artery disease. Positive clinical effects of ET are described in patients with congestive heart failure, heart valve surgery or intervention, adults with congenital heart disease, and peripheral arterial disease. Specific recommendations for risk stratification and adequate exercise prescription for continuous-, interval-, and strength training are given in detail. PI when added to ebCR did not show significant positive effects in general. There was a positive trend towards reduction in depressive symptoms for “distress management” and “lifestyle changes”. PE is able to increase patients’ knowledge and motivation, as well as behavior changes, regarding physical activity, dietary habits, and smoking cessation. The evidence for distinct ebCR programs in special patients’ groups is less clear. Studies on Tele-CR predominantly included low-risk patients. Hence, it is questionable, whether clinical results derived from studies in conventional ebCR may be transferred to Tele-CR. Conclusions: ET is the cornerstone of ebCR. Additional PI should be included, adjusted to the needs of the individual patient. PE is able to promote patients self-management, empowerment, and motivation. Diversity-sensitive structures should be established to interact with the needs of special patient groups and gender issues. Tele-CR should be further investigated as a valuable tool to implement ebCR more widely and effectively.